Recent developments and future prospects of magnesium–sulfur batteries - Wang, Liping; Riedel, Sibylle; Drews, Janina; Zhao-Karger, Zhirong (Frontiers in Batteries and Electrochemistry, 2024)
Rechargeable magnesium (Mg) batteries are promising candidates for the next-generation of energy storage systems due to their potential high-energy density, intrinsic safety features and cost-effectiveness. Among the various electrochemical couples, the combination of an Mg anode with a sulfur (S) cathode stands out as an attractive option, as it offers a remarkable theoretical volumetric energy density exceeding 3,200 Wh L–1. However, owing to the unique properties of Mg-ion electrolytes, Mg polysulfides and the surface passivation of Mg metal anodes, the development of Mg–S batteries is facing multiple challenges. In this review, recent advancements in designing efficient electrolytes for Mg–S battery systems are summarized. Apart from electrolytes, we also discuss the progress made in fabricating new S cathode composites, Mg anodes and functional separators, focusing on their roles in addressing the critical issues of the Mg–S systems. Finally, it is worth pointing out that the collaborative research combining experimental investigations and theoretical modelling could provide deeper insights into the mechanisms of Mg–S battery systems and promote their development. Overall, the comprehensive insights about the S-redox reaction, polysulfide shuttle problems and degradation mechanism in Mg–S batteries are discussed, which is of profound importance for creating solutions to enhance the overall performance of Mg–S batteries. This review aims to providing an overview of the current state of the research to stimulate innovative thoughts on the fundamental guidelines for facilitating development of Mg–S batteries.